2002
DOI: 10.1007/s11882-002-0074-2
|View full text |Cite
|
Sign up to set email alerts
|

Dust mite allergens: Ecology and distribution

Abstract: The most important allergy-causing mites found in homes worldwide are the house dust mites Dermatophagoides farinae, D. pteronyssinus, Euroglyphus maynei, and the storage mite Blomia tropicalis. Most homes contain multiple species. The most prevalent mite species and allergen in homes differ geographically, between homes within a geographical region, and among areas within a home. Therefore, it is important to know which mite species are present in a geographical area when performing diagnostic testing and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 101 publications
6
99
1
3
Order By: Relevance
“…1 Regions with a few months of relative humidity below 50% have low infestations. 2 In temperate regions, Dermatophagoides pteronyssinus, Dermatophagoides farinae, and Euroglyphus maynei (family: Pyroglyphidae) are the most commonly species found. In tropical and subtropical areas, Blomia tropicalis (family Glycyphagidae) and D. pteronyssinus are the most frequent species, while D. farinae is rarely found.…”
Section: Introductionmentioning
confidence: 99%
“…1 Regions with a few months of relative humidity below 50% have low infestations. 2 In temperate regions, Dermatophagoides pteronyssinus, Dermatophagoides farinae, and Euroglyphus maynei (family: Pyroglyphidae) are the most commonly species found. In tropical and subtropical areas, Blomia tropicalis (family Glycyphagidae) and D. pteronyssinus are the most frequent species, while D. farinae is rarely found.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, la presencia de las demás especies ha sido reportada en varios trabajos por diversos investigadores, lo cual puede estar sujeto a factores climáticos que no son completamente acertados dada su amplia variabilidad por ciudad, localidad o microambiente. En general, una humedad relativa alrededor del 55% es suficiente para la supervivencia de los ácaros del polvo [20].…”
Section: Resultados Y Discusiónunclassified
“…Se debe tener en cuenta que además de muestrear el número de ácaros por gramo de polvo, es importante determinar la cantidad de alér-genos [20,21].…”
Section: Resultados Y Discusiónunclassified
“…C. lactis can be found in sugary foods, such as white sugar, brown sugar, fruit sugar, biscuits, Shaqima, pastries, yogurt, candied fruit, prunes, dried plum, red dates, black dates, dried persimmons and the like (14,15). It can also grow and reproduce even if its whole body is soaked into the sugar solution (16). It was reported that, when C. lactis was reared in a tank using Cuban sugar as feeds, it was capable of surviving in a life cycle of some 13 to 18 days in temperature of 25 °C ± 1 °C with relative humidity of 75% (17).…”
Section: Discussionmentioning
confidence: 99%